Human-Metaverse Interaction in TVET: Research Trends and Future Directions - Ariawan, I Made Bambang; Abd Kadir, Shamsiah; Hadiana, Ana; Mohd Lokman, Anitawati (Journal of Technical Education and Training, 2025)
Technical and Vocational Education and Training (TVET) is swiftly advancing to integrate digital and immersive technologies, equipping learners for prospective employment markets. The metaverse, a shared virtual environment facilitating real-time interactions between individuals and digital entities, is an emerging technology impacting TVET. As Metaverse applications proliferate, they are anticipated to transform training techniques, skill acquisition, and workforce preparedness in Technical and Vocational Education and Training (TVET). A comprehensive analysis of prior studies on Human-Metaverse Interaction (HMI) is essential for grasping these implications. This study performs a bibliometric analysis of HMI, pinpointing essential topics, authors, publications, and trends within this domain. Primary bibliographic data is obtained from the Scopus database using keyword searches and quantitatively examined using bibliometric approaches in VOSviewer software. The analysis examines publication volume, thematic content, national connections, and keyword frequencies to delineate the intellectual framework of HMI research. Research findings reveal an increasing emphasis on virtual reality, augmented reality, and metaverse-related classifications, while highlighting deficiencies in domains like human-robot interaction and social virtual reality. This study offers significant insights for TVET educators and professionals, emphasizing how breakthroughs in HMI research might influence curriculum design, pedagogical approaches, and workforce readiness for a metaverse-oriented future.